McDowell’s communication intention theory Vs. Nyāya’s structure of understanding (Śābdabodha) - Bharti, Ruby; Tewari, Anil Kumar (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, I discuss that Śābdabodha and the Mc Dowell’s Communication intentionist theories are related each other. Śābdabodha is a process of understanding in which first we process the speaker’s verbalizing cognition and subsequently then encode it through a medium (i.e. Sentence). Secondly, a hearer must know that medium of instruction and get a same knowledge which the speaker had. It is viewed a two-way process of Speaker and the hearer and then we reach into certain understanding i.e. Śābdabodha. On the other hand, McDowell’s communication-intention theory which contends that the mutual awareness of intentions is a characteristic of human communication in transmitting knowledge on the basis of the reductive analysis of the concept of meaning. Both these concepts and theories face the problem of understanding in the communication. As an addition, Nyāya process of understanding includes the five stages of sentential meaning to generate the Śābdabodha. However, this paper is an attempt the Nyāya philosophy of language and its relation with the western philosopher McDowell’s Communication intentionist theory.